Erythritol alters phosphotransferase gene expression and inhibits the in vitro growth of Staphylococcus coagulans isolated from canines with pyoderma - Onishi-Sakamoto, Saki; Fujii, Tadashi; Watanabe, Keito; Makida, Reina; Iyori, Keita; Toyoda, Yoichi; Tochio, Takumi; Nishifuji, Koji (Frontiers in Veterinary Science, 2024)
Staphylococcus coagulans (SC) belongs to a group of coagulase-positive staphylococci occasionally isolated from the skin lesions of dogs with pyoderma. We recently revealed that erythritol, a sugar alcohol, inhibited the growth of SC strain JC7470. This study investigated the molecular mechanisms involved in this growth inhibition of JC7470 by erythritol to determine whether erythritol inhibits the growth of SC isolated from the skin of dogs with pyoderma. Comprehensive analysis of the gene expression of JC7470 in the presence of erythritol revealed that erythritol upregulated the expression of glcB and ptsG genes, both of which encode phosphotransferase system (PTS) glucoside-and glucose-specific permease C, B, and A domains (EIICBA), respectively, associated with sugar uptake. Moreover, erythritol suppressed in vitro growth of all 27 SC strains isolated from the skin lesions of canine pyoderma, including 13 mecA gene-positive and 14 mecA gene-negative strains.Finally, the growth inhibition of the SC clinical isolates by erythritol was restored by the addition of glucose. In summary, we revealed that erythritol promotes PTS gene expression and suppresses the in vitro growth of SC clinical isolates from dogs with pyoderma.Restoration of the erythritol-induced growth inhibition by glucose suggested that glucose starvation may contribute to the growth inhibition of SC.